2013
DOI: 10.1590/s0100-06832013000300010
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic quantification of soil phosphorus forms by 31p-nmr after nine years of organic or mineral fertilization

Abstract: SUMMARYLong-standing applications of mineral fertilizers or types of organic wastes such as manure can cause phosphorus (P) accumulation and changes in the accumulated P forms in the soil. The objective of this research was to evaluate the forms of P accumulated in soils treated with mineral fertilizer or different types of manure in a long-term experiment. Soil was sampled from the 0-5 cm layer of plots fertilized with five different nutrient sources for nine years: 1) control without fertilizer; 2) mineral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Pyrophosphate and polyphosphate concentrations were not significantly affected by P fertilization (Table 7). Similar results were obtained by Condron et al (1985), Gatiboni et al (2013), and Cade-Menun et al (2017) with long-term fertilized soils. Pyrophosphate is a short-chain polyphosphate (n = 2), and is believed to be a product of biological P cycling in soils (Condron et al 2005).…”
Section: Phosphorus Compounds Identified By 31 P-nmr and Their Cyclinsupporting
confidence: 88%
See 1 more Smart Citation
“…Pyrophosphate and polyphosphate concentrations were not significantly affected by P fertilization (Table 7). Similar results were obtained by Condron et al (1985), Gatiboni et al (2013), and Cade-Menun et al (2017) with long-term fertilized soils. Pyrophosphate is a short-chain polyphosphate (n = 2), and is believed to be a product of biological P cycling in soils (Condron et al 2005).…”
Section: Phosphorus Compounds Identified By 31 P-nmr and Their Cyclinsupporting
confidence: 88%
“…Solution 31 P nuclear magnetic resonance spectroscopy ( 31 P-NMR) is an advanced spectroscopic technique widely used to identify P compounds in soil extracts (Cade-Menun and Preston 1996;Cade-Menun 2005; Cade-Menun and Liu 2014). Gatiboni et al (2013) assessed the P compounds identified by 31 P-NMR spectroscopy in a Brazilian soil treated with mineral P fertilizer for 9 yr. They reported an accumulation of P i and inositol phosphate in the top 5 cm soil depth.…”
Section: Introductionmentioning
confidence: 99%
“…The high protein loading at the surface reduces the achievable resolution. 55 (this peak cannot be attributed to betaglycerophosphate because it exhibits a higher chemical shift 56 ). Mono-acid phosphates were shown to adopt a large range of chemical shifts, depending on the surroundings ions.…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that 31 P NMR is the most reliable method for the detection and quantification of polyphosphate species in environmental samples. In 2013, Gatiboni et al [104] performed quantification using 31 P NMR to study soil phosphorus forms after 9 years of organic, such as manure, or mineral fertilization. They showed that the use of fertilizers over 9 years did not change the soil phosphorus forms but influenced their concentration.…”
Section: E G Alves Filho L M Alexandre E Silva and A G Ferreirmentioning
confidence: 99%